Multidetector Computed Tomographic Characterization of a Rare Retroperitoneal Mass in the Left Psoas Compartment - Ramanan, Rochita Venkata; Krishnan, Elankumaran; Menon, Maya; Shivanandan, Ponneyinchelvi (Journal of Gastrointestinal and Abdominal Radiology, 2018)
We discuss a case of a rare, large, left-sided retroperitoneal mass that presented a diagnostic difficulty in characterization both radiologically and pathologically. We analyze the imaging findings in a step-by-step manner to understand its structure of origin, components, and tissue characterization. Intraoperative images are correlated with multidetector computed tomographic (CT) scan images to demonstrate spatial orientation. A discussion of the pathological findings, and conclusions are made. This discussion highlights the methodology by which radiologic diagnosis is made on multidetector CT scans.
Keywords: Keywords; multidetector computed tomography; primary ureteric sarcoma; retroperitoneal sarcoma; transitional cell carcinoma; psoas sarcoma; psoas space; retroperitoneum